Probing the epoch of reionization - Griffiths, Alex (2021)
The first generation of stars and galaxies are formed under gravitational collapse due to perturbations seeded from quantum fluctuations in the early Universe. These sources emit ionizing radiation, carving out ionized regions of the neutral intergalactic medium. With the subsequent formation and evolution of these primordial systems, ionized regions expand and overlap such that they eventually permeate throughout the entire universe, bringing an end to the dark ages and ushering in the epoch of reionization. Despite its pivotal role, the epoch of reionization lies mostly beyond the current observational capabilities and as such, is one of the least understood periods in the history of the Universe.